2016
DOI: 10.11124/jbisrir-2016-002655
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of tobacco intervention education in health professional students’ practice

Abstract: The objective of this review is to examine the effectiveness of entry-level education on smoking cessation or prevention and tobacco-dependence interventions on health professional student practice in promoting client health and on client smoking cessation behaviors.The specific review question to be addressed: what is the effect of entry-level tobacco dependence education on: (1) health professional students' knowledge and skills and self-efficacy, (2) performance of tobacco prevention and cessation intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…It is seen that our study ranks second with 19.4% (this rate was 22.8% if new beginners were not included). The studies here show that, although the average prevalence is relatively below 27.8%, one out of 4-5 physicians still smokes [9]. Additionally; we found that a peak similar to that seen in the grade-2 in our study was also present in Yaskiran's study (Yaskiran, 2020).…”
Section: Iii) Discussionsupporting
confidence: 77%
“…It is seen that our study ranks second with 19.4% (this rate was 22.8% if new beginners were not included). The studies here show that, although the average prevalence is relatively below 27.8%, one out of 4-5 physicians still smokes [9]. Additionally; we found that a peak similar to that seen in the grade-2 in our study was also present in Yaskiran's study (Yaskiran, 2020).…”
Section: Iii) Discussionsupporting
confidence: 77%
“…This systematic review followed an a priori published protocol [71]. The protocol was registered with the international prospective register of systematic reviews (PROSPERO) on 8 August 2016 as CRD42016044106.…”
Section: Methodsmentioning
confidence: 99%
“…Two independent reviewers critically appraised all eligible quantitative papers selected for retrieval using the Cochrane Collaboration risk-of-bias tool [73,74] and the JBI critical appraisal instrument [71,72]. The critical appraisal results are in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…12 Other health care curricula have implemented smoking cessation programs coined the 5A's model (Ask, Advise, Assess, Assist, and Arrange). 13 This model uses a mnemonic to guide health care professionals in initiating a brief 10 minute intervention session with patients on how to quit smoking cigarettes; however, the curriculum is taught with a wide variety of teaching styles due to professors expressing low self-confidence in knowledge and doubt in the ability to initiate change in patients. 13,14 This insecure foundation on the 5A's model has been shown to lead to improper use in health care practice.…”
Section: Literature Evaluationmentioning
confidence: 99%
“…13 This model uses a mnemonic to guide health care professionals in initiating a brief 10 minute intervention session with patients on how to quit smoking cigarettes; however, the curriculum is taught with a wide variety of teaching styles due to professors expressing low self-confidence in knowledge and doubt in the ability to initiate change in patients. 13,14 This insecure foundation on the 5A's model has been shown to lead to improper use in health care practice. 15,16 One study recorded 38 physicians during their tobacco cessation counseling sessions with 32% of physicians not asking or assessing the patient's current smoking status, thus defeating the purpose of the 5A's mnemonic.…”
Section: Literature Evaluationmentioning
confidence: 99%